Utilizing Emerging Technology Trends and Artificial Intelligence in Higher Education - Moncayo Cueva, Hugo Luis; Cuesta-Chávez, Giovanna; Ramírez, Andrea; Zambrano Pintado, Ruth Narciza (Journal of Higher Education Theory and Practice, 2024)
Today’s higher education is characterized by accelerated technological advances and a growing need for adaptation. This research focuses on the utilization of emerging technological trends and artificial intelligence (AI) as innovative solutions to enhance the quality and effectiveness of teaching and learning. The problem lies in the necessity of strategically harnessing the potential of emerging technologies and AI in higher education. The objective is to thoroughly examine the implementation of emerging technologies and artificial intelligence within the realm of higher education. A comprehensive systematic review was conducted, involving the analysis of 240 articles selected from searches within the Scopus, SpringerLink, and Web of Science databases the selection process employed rigorous inclusion and exclusion criteria, to achieve this, we utilized the PRISMA methodology with a systematic approach. Consequently, our findings indicate that the integration of emerging technologies and artificial intelligence in higher education offers valuable guidance for decision-making and enhances the effectiveness of educational strategies in the digital era.